Africa Adapt - Harvey, Blane; Ensor, Jonathan; Carlile, Liz; Garside, Ben; Patterson, Zachary; Naess, Lars Otto (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
Africa Adapt is an online/offline knowledge sharing platform that was designed to share local African knowledge and experience on climate change. It was set up after a scoping of partners, through a number of regional forums in Africa, to discuss the idea of a knowledge hub and to identify what was needed and who best could develop and run it. Phase 1 was launched in 2008 by IDS with partners ENDA, FARA and ICPAC. In 2011 there was an evaluation of what has worked and not worked and re-launch with IDS stepping back to a capacity support role and the partnership being devolved to lead partner ENDA to ensure implementation.